1994
DOI: 10.1115/1.2919460
|View full text |Cite
|
Sign up to set email alerts
|

Design of the Ball Screw Mechanism for Optimal Efficiency

Abstract: This paper develops theories for evaluating the efficiency of the ball screw mechanism and additionally, for designing this mechanism. Initially, a quasi-static analysis, which is similar to that of the early work in this area, is employed to evaluate efficiency. Dynamic forces, which are neglected by the quasi-static analysis, will have an effect on efficiency. Thus, an exact theory based on the simultaneous solution of both the Newton-Euler equations of motion and the relevant kinematic equations is employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Wei [1][2][3] introduced the theory of differential geometry of curve to analyze the motion rules of a ball considering the effect of the elastic deformation of contact angle and found that the self-spin and rotational angular velocities of the ball have an approximately linear relationship with the rotational velocity of the screw. Lin et al [4][5] confirmed the existence of both the rolling and sliding motions relative to each other between the ball and raceway during the operation of BSM and proposed a calculation model to estimate the transmission efficiency. Gnanamoorthy and Govindarajan [6][7] identified the slide/roll ratio of the contact point as the key factor influencing the wear velocity of the contact area.…”
Section: Introductionmentioning
confidence: 98%
“…Wei [1][2][3] introduced the theory of differential geometry of curve to analyze the motion rules of a ball considering the effect of the elastic deformation of contact angle and found that the self-spin and rotational angular velocities of the ball have an approximately linear relationship with the rotational velocity of the screw. Lin et al [4][5] confirmed the existence of both the rolling and sliding motions relative to each other between the ball and raceway during the operation of BSM and proposed a calculation model to estimate the transmission efficiency. Gnanamoorthy and Govindarajan [6][7] identified the slide/roll ratio of the contact point as the key factor influencing the wear velocity of the contact area.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, many studies have been conducted for the calculation of the friction torque and the coefficient of friction is usually considered as a fixed value in these studies. Lin et al 4 developed a theory to design the ball screw mechanism and evaluate the efficiency of the mechanism. A peak efficiency can be obtained when the coefficient of friction is equal to 0.075 based on their study.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al 9,10 presented two studies of the kinematics of ball screws to describe the ball motion and mechanical efficiency, which contributes to achieve the optimum design of ball screws. Based on Lin's study, Wei et al 11 studied the kinematics of a singlenut double-cycle ball screw by considering the friction force produced by a ball moving in an oil lubricant, in which both of the mechanical efficiency with and without oil lubrication were compared and discussed.…”
Section: Introductionmentioning
confidence: 99%